Fibrillated bacterial cellulose liquid carbene bioadhesives for mimicking and bonding oral cavity surfaces - Singh, Juhi (2022)
Topical treatments for oral wounds and infections exhibit weak adhesion to wet surfaces which results in short retention duration (6-8 hours), frequent dosing requirement and patient incompatibility. To address these limitations, aqueous composites made of fibrillated bacterial cellulose and photoactive bioadhesives are designed for soft epithelial surfaces. The aqueous composites crosslink upon photocuring within a minute and exhibit a transition from viscous to elastic adhesive hydrogels. The light-cured composites have shear moduli mimicking oral mucosa and other soft tissues. The tunable adhesion strength ranges from 3 to 35 kPa on hydrated tissue-mimicking surfaces (collagen film). The results support the application of bacterial cellulose hydrogel systems for potential treatment of mucosal wounds.